The Effect of Income of Farmers and Farm Laborers on Agricultural Economic Growth - Abyan Rai (Jurnal Ekonomi Pembangunan, 2021)
The agricultural sector plays an essential role in the economy of a country. This critical role cannot be separated from the main component of the farm sector, namely, farmers. To support economic growth and poverty alleviation through the agricultural industry, the welfare of farmers must be a concern. This study aims to analyze the effect of the income of farmers and farm laborers on agricultural economic growth. The method used is ECM with 24 quarterly data observations. The price index received by farmers approximates farmers' incomes, farm laborers' incomes are approximated by the daily real wages of farm laborers, and agricultural economic growth is approximated by the real GRDP of the agricultural sector. The results showed that the income of farmers and farm laborers during the research period had a positive trend. In the long-term and short-term equation, the payment of farmers and farm laborers has a significant positive effect on the economic growth of the agricultural sector. An increase in the income of farmers and farm laborers also followed the increase in agricultural economic development. These results can be used as a reference for the government to make policies to increase the income of farmers and farm laborers.